Osobennosti samoorganizacii škol'nikov-sportsmenov podrostkovogo vozrasta - Mochalova, M. S.; Nikitina, E. D. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article contains data about the level of formation of components, self-organizational of adolescent athletes studyingin a general school, shows the content of the components depending on their degree of formation on average, above average and below average levels. In the course of the study, it was revealed that in half of the schoolchildren, the components of self-organization were formed at an average level. In this way, adolescent athletes studying in a comprehensive school need targeteddevelopment and pedagogical support for the self-organization process.